The effects of an open and closed divertor on particle exhaust during edge-localized mode suppression by resonant magnetic perturbations in DIII-D - Unterberg, E.A; Schmitz, O; Evans, T.E; Maingi, R; Brooks, N.H; Fenstermacher, M.E; Mordijck, S; Moyer, R.A; Orlov, D.M (Nuclear fusion, 2010)
This paper compares the effects of divertor geometry on particle exhaust characteristics during the suppression of ELM using resonant magnetic perturbations (RMPs) on DIII-D. The subject is timely, particularly for ITER, because the combination of techniques to control or mitigate ELMs and control particle exhaust can provide confidence in the ability of an external pumping system to fully remove the particle exhaust. The differences between an open and closed divertor magnetic topology show a strong coupling of the perturbed strikepoint to the pumping manifold in closed divertor configurations, which can increase the particle exhaust by a factor of four. There is also an observed dependence on q 95 in this configuration, which is a common feature of RMP ELM suppression. Neutral density in both the active and non-active divertors is seen to increase during the RMP in the ISS configuration, and edge plasma conditions (i.e. n e,sep and midplane profile of D α ) are seen to increase in the closed divertor configuration. Finally, the pumping exhaust is also shown to have a strong dependence on local measurements of the recycling flux. These observations, when taken as a whole, point to a substantial change in the plasma edge conditions, i.e. near the LCFS, throughout the poloidal cross-section of the vacuum vessel. This is coincident with the application of the RMP affecting the pumping capability of the system.